Recent advances in isatin-derived hybrids: promising multifunctional agents for drug development - Aleksandar Dimkovski; Evgenija Mihajloska; Ana Poceva Panovska (Makedonsko Farmacevtski Bilten, 2025)
Isatin-based hybrids have emerged as promising candidates in medicinal chemistry due to their broad biological activities and structural versatility. This review outlines recent developments (2020–2025) in the design of isatin hybrids targeting cancer, neurodegenerative diseases, bacterial and mycobacterial infections, diabetes, inflammation, and viral diseases. Rational hybridization strategies have led to compounds with enhanced potency, multitarget activity, and improved pharmacokinetic profiles. Key structural modifications, especially at the N-1, C-3, and C-5 positions of the isatin core, have been crucial in optimizing biological efficacy. Several hybrids demonstrated superior activity compared to standard drugs, alongside favorable safety and pharmacodynamic and pharmacokinetic profiles. This overview highlights the therapeutic potential of isatin hybrids as versatile scaffolds for the development of next-generation multifunctional agents across diverse clinical areas.